Interfacial modification of high-loading sugar palm fiber/unsaturated polyester biocomposites using alkali–vinyltrimethoxysilane treatment - Fahriadi Pakaya; Yurika Nantan; Marinus S. Tappy; I Nyoman Subawa (Politeknik Negeri Lhokseumawe, 2026)
Natural fiber-reinforced polyester biocomposites are promising lightweight materials, but their performance is often limited by weak fiber–matrix interaction, especially at high fiber loading. This study investigates the effect of combined alkali–Vinyltrimethoxysilane (VTMS) treatment on the flexural and physical properties of sugar palm fiber-reinforced Unsaturated Polyester Resin (UPR) biocomposites. Untreated fiber composites (IU/UPR), NaOH-treated fiber composites (IA/UPR), and NaOH–VTMS-treated fiber composites (IAS/UPR) were fabricated using the hand lay-up method at fiber loadings of 0–50 wt.%. The results showed that IAS/UPR exhibited the best overall performance, particularly at 50 wt.% fiber loading, achieving a flexural strength of 110.59 MPa, compared with 37.20 MPa for IU/UPR and 50.60 MPa for IA/UPR. IAS/UPR also showed lower water absorption, higher density, and lower porosity. Two-way ANOVA confirmed that fiber treatment, fiber loading, and their interaction significantly affected flexural strength, water absorption, and porosity. FTIR analysis indicated the reduction of hemicellulose and lignin-related components, while SEM observations showed improved matrix coverage, fewer interfacial gaps, and reduced fiber pull-out. These results indicate that alkali–VTMS treatment improves interfacial compatibility and extends the effective fiber-loading range of sugar palm fiber/UPR biocomposites.